Peran Desain Pembelajaran dalam Kurikulum Merdeka: Pendekatan dan Implementasi - Liza, Nova; Zurhidayati, Zurhidayati; Fadriati, Fadriati (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This article explores the important role of learning design in the implementation of the independent curriculum in Indonesia. Learning design provides a structured framework for the educational process, ensures teaching effectiveness, and achieves expected learning objectives. With this approach, teachers can design learning that is relevant, interesting, and in accordance with the needs of students. This research uses a qualitative approach with a literature study method, which is also known as library research. The data sources used in this study consist of secondary data sources obtained from journals or articles, as well as books related to independent curriculum learning design. The main source of article search is articles sourced from Google Scholar. Data analysis is carried out qualitatively, through the stages of data reduction, data presentation, and conclusions. The results of the analysis show that good learning design aims to develop the knowledge, skills, and attitudes of students in accordance with the demands of the times, with the hope that the learning process will be more meaningful, fun, and have a positive impact